Problem Moralitas Guru Pendidikan Agama Islam Sebagai Pendidik Profesional Dalam Membentuk Membentuk Generasi Berakhlakul Karimah - Muslikh, Muslikh (Universitas Majalengka, 2024)
The role of Islamic Religious Education teachers is very strategic, they create future generations who are expected to be agents of change in society. PAI teachers as professional educators have competence in the field of Islamic knowledge and have the integrity to maintain moral values and commitment to their profession. His status as a professional educator attaches to him the values of truth, goodness and beauty. Ideally, the height of a person's abilities is directly proportional to his moral values. However, it becomes a problem if ethical and aesthetic values have been removed from the values of scientific truth held by PAI teachers. This research aims to provide the teacher's code of ethics with integrity that is inherent in their status and position as professional educators. This qualitative research uses a library method with a hermenomic approach to analysis. This research will show that PAI teachers as professional educators are not free of values, they adhere to a code of ethics as a norm of integrity.